Decrease expression and clinicopathological significance of miR-148a with poor survival in hepatocellular carcinoma tissues - Ajdarkosh, Hossein (Diagn Pathol, 2015)
BACKGROUND: Hepatocellular carcinoma (HCC) is a leading cause of cancer-related death worldwide, mainly due to its high rates of postoperative recurrence and metastasis. Please remove, it currently ranks as the third most common cause of cancer-related deaths. MiRNAs are a set of small, single-stranded, non-coding RNA molecules that negatively regulate gene expression at the post-transcriptional level. In this study, we demonstrated the down-regulation of miR-148a in HCC and non-cancerous tissues using qRT-PCR. METHODS: Ninety six HCC samples and their noncancerous normal liver tissues were collected. Total mRNA including miRNA was extracted, and miR-148a expression was determined using qRT-PCR. Furthermore, the correlation between the miR-148a expression and clinicopathological parameters was investigated. RESULTS: The result showed that reduction of miR-148a expression was associated with TNM stage, metastasis, and number of tumor nodes. Multivariate Cox proportional hazards model analysis showed that low expression of miR-148a was independently associated with recurrence of HCC in the current study. Moreover, our result showed that lower expression in tumor tissues in comparison with corresponding normal control tissues. CONCLUSION: Down-regulation of miR-148a is related to HCC carcinogenesis and deterioration of HCC. MicroRNA-148a may act as a suppressor miRNA of HCC, and it is therefore a potential prognostic biomarker for HCC patients.